ANALISIS FAKTOR KONFIRMATORI DIMENSI KUALITAS PELAYANAN (SERVICE QUALITY) - Subandi, Subandi (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
The purpose of this study was to determine the application of confirmatory second order factor analysis in testing the validity and reliability of the service quality construct consisting of the dimensions of reliability, assurance, tangible, empathy, and responsiveness. The sample in this study were customers of Bank X in Yogyakarta with a total of 150. The sampling technique used purposive sampling. Data analysis with the help of the AMOS 20 program. The conclusion that can be drawn is that all indicators forming the latent variables of service quality dimensions are valid and reliable. The greatest value of the dimension constructing service quality is the dimension of responsiveness, then assurance, empathy, reliability and tangible. Overall the model has met the criteria of a good goodness of fit.